diff --git a/sols.tex b/sols.tex
index 988f55b..2adbb8a 100755
--- a/sols.tex
+++ b/sols.tex
@@ -15,7 +15,7 @@
\usepackage{tabls}
%TCIDATA{OutputFilter=latex2.dll}
%TCIDATA{Version=5.50.0.2960}
-%TCIDATA{LastRevised=Wednesday, May 25, 2016 13:06:05}
+%TCIDATA{LastRevised=Wednesday, May 25, 2016 13:28:10}
%TCIDATA{SuppressPackageManagement}
%TCIDATA{}
%TCIDATA{}
@@ -13643,11 +13643,12 @@ \subsection{Prelude to Laplace expansion}
From (\ref{eq.det.eq.2}), we obtain%
\begin{align*}
-\det A & =\sum_{\sigma\in S_{n}}\left( -1\right) ^{\sigma}\underbrace{\prod
-_{i=1}^{n}a_{i,\sigma\left( i\right) }}_{=\left( \prod_{i=1}^{n-1}%
-a_{i,\sigma\left( i\right) }\right) a_{n,\sigma\left( n\right) }}%
-=\sum_{\sigma\in S_{n}}\left( -1\right) ^{\sigma}\left( \prod_{i=1}%
-^{n-1}a_{i,\sigma\left( i\right) }\right) a_{n,\sigma\left( n\right) }\\
+\det A & =\sum_{\sigma\in S_{n}}\left( -1\right) ^{\sigma}%
+\underbrace{\prod_{i=1}^{n}a_{i,\sigma\left( i\right) }}_{=\left(
+\prod_{i=1}^{n-1}a_{i,\sigma\left( i\right) }\right) a_{n,\sigma\left(
+n\right) }}=\sum_{\sigma\in S_{n}}\left( -1\right) ^{\sigma}\left(
+\prod_{i=1}^{n-1}a_{i,\sigma\left( i\right) }\right) a_{n,\sigma\left(
+n\right) }\\
& =\sum_{\substack{\sigma\in S_{n};\\\sigma\left( n\right) =n}}\left(
-1\right) ^{\sigma}\left( \prod_{i=1}^{n-1}a_{i,\sigma\left( i\right)
}\right) \underbrace{a_{n,\sigma\left( n\right) }}_{\substack{=a_{n,n}%
@@ -13658,7 +13659,7 @@ \subsection{Prelude to Laplace expansion}
(\ref{pf.thm.laplace.pre.1}))}}}\\
& \ \ \ \ \ \ \ \ \ \ \left( \text{since every }\sigma\in S_{n}\text{
satisfies either }\sigma\left( n\right) =n\text{ or }\sigma\left( n\right)
-\neq n\text{ (but not both)}\right) \\
+\neq n\text{ (but not both)}\right) \\
& =\sum_{\substack{\sigma\in S_{n};\\\sigma\left( n\right) =n}}\left(
-1\right) ^{\sigma}\left( \prod_{i=1}^{n-1}a_{i,\sigma\left( i\right)
}\right) a_{n,n}+\underbrace{\sum_{\substack{\sigma\in S_{n};\\\sigma\left(
@@ -13686,14 +13687,14 @@ \subsection{Prelude to Laplace expansion}
Assume that%
\begin{equation}
a_{i,n}=0\ \ \ \ \ \ \ \ \ \ \text{for every }i\in\left\{ 1,2,\ldots
-,n-1\right\} .\label{eq.cor.laplace.pre.col.ass}%
+,n-1\right\} . \label{eq.cor.laplace.pre.col.ass}%
\end{equation}
Then, $\det A=a_{n,n}\cdot\det\left( \left( a_{i,j}\right) _{1\leq i\leq
n-1,\ 1\leq j\leq n-1}\right) $.
\end{corollary}
\begin{proof}
-[Proof of Corollary \ref{cor.laplace.pre.col}.] We have $n-1\in\mathbb{N}$
+[Proof of Corollary \ref{cor.laplace.pre.col}.]We have $n-1\in\mathbb{N}$
(since $n$ is a positive integer).
We have $A=\left( a_{i,j}\right) _{1\leq i\leq n,\ 1\leq j\leq n}$, and thus
@@ -13705,7 +13706,8 @@ \subsection{Prelude to Laplace expansion}
$a_{i,j}$) yields
\begin{equation}
\det\left( A^{T}\right) =a_{n,n}\cdot\det\left( \left( a_{j,i}\right)
-_{1\leq i\leq n-1,\ 1\leq j\leq n-1}\right) .\label{pf.cor.laplace.pre.col.1}%
+_{1\leq i\leq n-1,\ 1\leq j\leq n-1}\right) .
+\label{pf.cor.laplace.pre.col.1}%
\end{equation}
@@ -13736,12 +13738,12 @@ \subsection{Prelude to Laplace expansion}
Now,%
\begin{align*}
-\det A & =\det\left( A^{T}\right) =a_{n,n}\cdot\underbrace{\det\left(
+\det A & =\det\left( A^{T}\right) =a_{n,n}\cdot\underbrace{\det\left(
\left( a_{j,i}\right) _{1\leq i\leq n-1,\ 1\leq j\leq n-1}\right) }%
_{=\det\left( \left( a_{i,j}\right) _{1\leq i\leq n-1,\ 1\leq j\leq
n-1}\right) }\ \ \ \ \ \ \ \ \ \ \left( \text{by
-(\ref{pf.cor.laplace.pre.col.1})}\right) \\
-& =a_{n,n}\cdot\det\left( \left( a_{i,j}\right) _{1\leq i\leq n-1,\ 1\leq
+(\ref{pf.cor.laplace.pre.col.1})}\right) \\
+& =a_{n,n}\cdot\det\left( \left( a_{i,j}\right) _{1\leq i\leq n-1,\ 1\leq
j\leq n-1}\right) .
\end{align*}
This proves Corollary \ref{cor.laplace.pre.col}.
@@ -22050,7 +22052,10 @@ \subsection{\label{sect.desnanot}The Desnanot-Jacobi identity}
\begin{proof}
[Proof of Lemma \ref{lem.desnanot.AB.tech}.]We have $n-1\in\mathbb{N}$ (since
-$n$ is a positive integer).
+$n$ is a positive integer). Also, $u